Rational use of chemotherapeutic agents - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Rational drug use can be defined as the most appropriate use of drugs for particular clinical needs, in doses necessary for an individual patient, for an adequate duration, and at the possible lowest cost. Cancer patients undergo series of complex treatment regimens to treat and manage the disease, and encounter treatment-related complications as well as they present comorbidities. The cost of medications has a large burden on the health care system. Rational use of all drugs in this context becomes a priority in order to provide the best therapeutic outcomes with minimum damage to patients, their families and the community as a whole. The toxicity and narrow therapeutic index of most antineoplastic medications and some palliative care drugs make patient-based dosing a critical issue in oncology. Pharmacists are one of the main branches of the health care system. In most health care systems, they are responsible for the supply and preparation of chemotherapy agents and other medications. They provide medication management services and provide health care professionals, patients and families with all necessary drug information that will improve patients' therapeutic outcomes and quality of life. Pharmacists well-trained in oncology help to achieve rational use of medications and reduce the incidence of harm to the patient. © 2021 Nova Science Publishers, Inc. All rights reserved.
Keywords: Mechanism of action; Monitoring parameters; Rational drug use; Side effects; Warnings